An Arduino Based Safety Stick for Blind People - Sadiq, Ayat Kareem; Abdalkahder, Sura Saddam; Jabbar, Shahad Jamal Abdul; Talab, Rania Bassam; Majeed, Mohammed Ali Nadim; Abbas, Ayaa Khuder (American Journal of Botany and Bioengineering, 2025)
The mobility and independence of visually impaired individuals remain significant challenges due to environmental obstacles and the absence of reliable assistive devices. Current mobility aids lack integrated technological features to enhance safety and navigation. This study introduces an Arduino-based smart stick designed for blind people, incorporating ultrasonic sensors for obstacle detection, water sensors for hazard identification, and heart pulse sensors for user health monitoring. The system employs an MP3 module for audio feedback and a GPS module for location tracking. Findings indicate that the device provides accurate obstacle detection, real-time alerts, and improved navigation assistance, enhancing the safety and autonomy of visually impaired users. The results suggest that the proposed system offers a cost-effective and portable solution for blind mobility, with implications for future developments integrating GSM communication and solar-powered functionalities.